O modelo TPACK em uma licenciatura em matemática de uma universidade pública de Teixeira de Freitas/BA - Souza, Mariangela Silva (2024)
Qualitative research, defined as a case study, aims to answer the following guiding question: What categories of Technological Pedagogical Content Knowledge (TPACK) are present in the teacher training program for Mathematics at the State University of Bahia, Campus X, considering students' understanding and the curriculum of the course? Based on the studies of Shulman (1987) and Mishra and Koehler (2006), our purpose is to identify the TPACK knowledge present in the undergraduate program by analyzing the Course Recognition Plan (PRCLM) for the Mathematics Teaching Degree and the students' understanding. In addition to analyzing the PRCLM, where we classified the subjects according to their syllabi within the TPACK categories, we used questionnaires and semi-structured interviews to collect data from students. We employed Textual Discursive Analysis (TDA) as outlined by Moraes and Galiazzi (2020) for interpreting the interviews. Seven students from the Mathematics Teaching Degree, from the seventh and ninth semesters, participated in our research. The results revealed that, despite the perceived emphasis on Content Knowledge in the program, the other components of the TPACK framework were identified within the subjects of the degree. According to the students, the organization and curricular practice present in the program have facilitated the integration of TPACK knowledge throughout the course, fostering the development of Technological, Pedagogical, and Content knowledge among future mathematics teachers.